Drawing Spirits in the Sand: Performative Storytelling in the Digital Age - Tafler, David I. (Religions, 2019)
For First Nations people living in the central desert of Australia, the performance of oral storytelling drawing in the sand drives new agency in the cultural metamorphosis of communication practices accelerated by the proliferation of portable digital devices. Drawing on the ground sustains the proxemic and kinesthetic aspects of performative storytelling as a sign gesture system. When rendering this drawing supra-language, the people negotiate and ride the ontological divide symbolized by traditional elders in First Nations communities and digital engineers who program and code. In particular, storytelling's chronemic encounter offsets the estrangement of the recorded event and maintains every participants' ability to shape identity and navigate space-time relationships. Drawing storytelling demonstrates a concomitant capacity to mediate changes in tradition and spiritual systems. While the digital portals of the global arena remain open and luring, the force enabled by the chiasmic entwinement of speech, gesture and sand continues to map the frontier of First Nations identity formation and reformation.